Resistência de Conyza bonariensis e Conyza canadensis (Asteraceae) a herbicidas - Reis, Lucas Casimiro (Universidade Federal de São Carlos, 2020)
The species Conyza bonariensis and Conyza canadensis, popularly known like clove, are plants belonging to the Asteraceae family that have great importance in modern agriculture due to the levels of economic damage caused by their interference in the development of culture. With the emergence of biotypes resistant to the herbicide glyphosate, one of the most widely used herbicides in worldwide, the management of these plants has become increasingly problematic, requiring continuous management and the use of new control and alternative herbicides to control this weed
Resistence of Conyza bonariensis AND Conyza canadensis (Asteraceae) to herbicides
Keywords: Buva; Resistência; Manejo; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA